Original Institutional Economics Outside the United States: The Brazilian Chapter. Issue 2 (3rd April 2022) - Almeida, Felipe; Brites, Maríndia
Abstract: This study intends to examine the roots of Original Institutional Economics (OIE) in Brazil. We rely on two methodologies to analyze the dissemination of OIE in Brazil: a bibliometric study, which identifies key Brazilian authors who published their studies in the Journal of Economic Issues (JEI); and an analysis of academic curriculum vitae (CVs) through an online compilation of Brazilian researchers' CVs, the Lattes Platform, where it is possible to identify researchers by field. After identifying the Brazilian institutionalists, we study their writings, professor–student relationship, co- authorship, and teaching. We identify three groups of Brazilian institutionalists: (1) a heterogeneous group in São Paulo, (2) a group in Paraná that is concentrated at the same university, and (3) a cohesive group in Rio Grande do Sul.